A fresh look at business cycle synchronisation in the euro area - Gayer, Christian; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2007)
This paper revisits the issue of business cycle synchronisation in the euro area looking back on more than eight years of EMU experience. The dispersion of output gaps across Member States has reached historically low levels since around 2002. Yet, this observation seems to reflect a general decrease in the amplitude of cyclical fluctuations rather than a continued increase in business cycle synchronisation. Using cross-country correlations, the mean level of synchronisation of national cycles within the currency union since 1999 is found to be overall high, though not higher than in the first half of the nineties. Around 2003, the level of cross-country synchronisation experienced a quite abrupt decrease. This picture is shared between several measures of the business cycle. A rebound and partial recovery of cross-country synchronisation is indicated from around 2004 onwards. The observed dip in synchronisation thus appears to be a transitory phenomenon, partly rooted in a recurrent pattern of falling business cycle synchronisation in early recovery phases.
Economic Papers